Synthetic CDCA Derivatives-Induced Apoptosis of Stomach Cancer Cell Line SNU-1 Cells - Moon, Bongkyung (Korean Cancer Association, 2004)
PURPOSE: This study was conducted to explore whether CDCA derivatives induce apoptosis in a stomach cancer cell line, and to dissect the detailed mechanism underlying apoptosis. MATERIALS AND METHODS: The human stomach cancer cell line, SNU-1, cells were treated with the synthetic CDCA derivatives, HS-1199 and HS-1200. DNA and mitochondrial stains were used to detect apoptotic cells by fluorescence imaging or flow cytometry. The caspase-3 activity was measured by Western blotting. RESULTS: Both the HS-1199 and HS-1200 induced decreased viabilities of the SNU-1 cells, in time-dependent manners. The CDCA derivatives demonstrated various apoptosis hallmarks, such as mitochondrial changes (reduction of MMP, cytochrome c release, and Smac/ DIABLO translocation), activation of caspase-3 (resulting in the degradation of PARP and DFF45), DNA fragmentation and nuclear condensation. CONCLUSION: The CDCA derivatives, HS-1199 and HS-1200, both induced apoptosis of the SNU-1 gastric cancer cells in caspase- and mitochondria-dependent fashions. Many important issues relating to their therapeutic applications remain to be elucidated.